Response Surface Methodology for Enhanced Keratinase and Disulphide Reductase Production by Bacillus subtilis CFB-09 for Cow Hoof Biodegradation - Adisa, M. F.; Akerele, A. A.; Adenika, J. B.; Aiyeminimowa, T. U.; Olajuyigbe, F. M. (Journal of Science, Technology and Innovation Research, 2026)
Keratinous wastes are resistant to biodegradation due to disulphide bonds present in keratin. Despite extensive work on keratinolytic microorganisms and keratinase involved in biodegradation, there is dearth of information on disulphide reductase responsible for breaking disulphide bonds. Hence, the need to investigate simultaneous production of keratinase and disulfide reductase by keratin degrading microorganisms, and to optimize biodegradation of keratinous wastes. In this study, Bacillus subtilis CFB-09 was screened for proteolytic and keratinolytic abilities using skimmed milk and cow hoof. Enzyme production was optimized using Box Benkhen Design response surface methodology (BBD-RSM) for enhanced degradation of cow hoof. Qualitative screening confirmed proteolytic and keratinolytic abilities of B. subtilis CFB-09 with clearance zones of 26 mm and 30 mm, respectively. Results revealed optimum enzyme production (39.37 U/mL) at 48 h of incubation of B. subtilis CFB-09. Optimal conditions for biodegradation of cow hoof were 37.5 oC, pH 8.0, and 1.0 % (w/v) for keratinase and 40 oC, pH 8.0, 1.5 % (w/v) for disulphide reductase, having activities of 406.04 U/mL and 139.71 U/mL, respectively. Remarkably, the best numerical solution from RSM for maximum enzyme production revealed a temperature of 35 °C, pH 8.2, and substrate concentration of 0.5 % (w/v) with desirability of 0.80. These numerical solutions yielded 526.85 U/mL and 151.14 U/mL of keratinase and disulphide reductase, respectively. The optimised conditions offer insight into enhanced degradation of keratin-rich cow hoof through improved enzymes co-production. These results provide sustainable tool for keratinous waste management, with applications in leather, detergent, and animal feed industries.